ANALISIS FRAMING KONFLIK ISRAEL PALESTINA DALAM PEMBERITAAN MEDIA AL-JAZEERA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study aims to describe Al Jazeera's media framing regarding the Palestinian Israeli conflict, which focuses on the population in Jerusalem which is raised in a document entitled "Jerusalem the Rock and the Hard Place: Israel, Trump and the Future of Jerusalem part I and Jerusalem the Rock and the Hard Place: Jerusalem can Jews, Christian, Muslim Live Together. The results showed that Al Jazeera media framed the documentary entitled "Jerusalem the Rock and the Hard Place part I and II". The framing of the film shows that the Palestinian population, represented by Muslims and Christians, is living under pressure from the Israeli government authorities, especially those who live in the territory of Jerusalem. Palestinians are victims of Israeli occupation who live in the confinement of the parapet, can at any time lose their citizenship status, are revoked from work, are threatened with the eviction of their homes, and do not have any political rights.